AgResults year 5 implementer induction and training (Group Two Presentation) - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2018)
Group Two giving their Presentation at the AgResults Year 5 Implementer Induction and Training at IITA Ibadan